Determination of Cd, Pb, and Cu in the Atmospheric Aerosol of Central East Antarctica at Dome C (Concordia Station) - Silvia Illuminati; Anna Annibaldi; Cristina Truzzi; Caterina Mantini; Eleonora Conca; Mery Malandrino; Giada Giglione; Matteo Fanelli; Giuseppe Scarponi (Molecules, 2021)
Trace heavy metals Cd, Pb, and Cu were determined (by square wave anodic stripping voltammetry) in aerosol samples collected at Dome C (the Italo-French Station Concordia), a remote site of the Central East Antarctic plateau, for which no data are available until now. During the Austral Summer 2005–2006, three PM10 high-volume impactors were installed in two locations nearby of Concordia station: the first one very close and downwind of the station (about 50 m north), the other two (very close to each other) in a ‘distant’ site, upwind of the station and close to the astrophysics tent (not used in that expedition) at ~800 m south of Station Concordia. For each sample, the availability of the mass of the aerosol collected (obtained by differential weighing carried out on site), in addition to the volume of the filtered air, allowed us to express results both in terms of metal mass fractions in the aerosol and in the usual way of metal atmospheric concentrations. Metal contents increased in the order Cd < Pb < Cu with the following ranges of values: Cd 1.0–8.4 µg g−1 (0.09–3.1 pg m−3), Pb 96–470 µg g−1 (12–62 pg m−3), and Cu 0.17–20 mg g−1 (0.027–2.4 ng m−3). From the metal temporal profiles obtained we estimated the following background values for the area of Dome C, expressed both in mass fractions and in atmospheric concentrations: Cd 1.2 ± 0.2 µg g−1 (0.24 ± 0.13 pg m−3), Pb (here fixed as upper limit) 113 ± 13 µg g−1 (21 ± 8 pg m−3), and Cu 0.91 ± 0.48 mg g−1 (0.12 ± 0.07 ng m−3). The highest values were observed in the first part of the season, and particularly for the site close to the station, possibly related to sample contamination linked to intense activity at the Concordia station connected with the beginning of the expedition, including aircraft arrivals/departures. Increments of up to 10 times (and even 20 times for Cu) were recorded with respect to the background values. The metal excesses of the contaminated over background samples were found approximately, except for Cu, in the same ...